Artificial Intelligence Driven Literacy Practices in Early Language Education: Praktik Literasi yang Didorong oleh Kecerdasan Buatan dalam Pendidikan Bahasa Awal - Ahmad Nurefendi Fradana; Nyoman Suwarta (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The integration of artificial intelligence (AI) into education has rapidly transformed learning environments, particularly in literacy education. Specific background: In primary schools, AI offers tools that support individualized learning and streamline instructional processes. Knowledge gap: However, limited research explores the sociocultural dynamics of AI-mediated literacy learning, especially in early education within Indonesian contexts. Aims: This study investigates the application of AI in reading and writing instruction at Muhammadiyah Primary School 1 Candi, Sidoarjo, through an educational ethnography and qualitative-descriptive approach. Results: Findings demonstrate that AI facilitates personalized literacy experiences, enhances student motivation, and improves instructional efficiency. Nonetheless, critical issues such as increased student dependency on automated systems, diminished verbal interaction, and the presence of cultural bias in AI-generated content were observed. Novelty: The study highlights the teacher’s evolving role not merely as a knowledge transmitter but as a facilitator of values and cultural mediator in AI-supported classrooms. Implications: It recommends the adoption of AI integration strategies that prioritize ethical awareness, cultural contextualization, and humanistic principles, contributing to the development of an inclusive and adaptive literacy education ecosystem for primary learners.Highlights: Highlights the sociocultural impacts of AI in early literacy. Reveals both benefits and ethical challenges of AI integration. Emphasizes the teacher’s role as a value-based content mediator. Keywords: Artificial Intelligence, Literacy Education, Primary School, Educational Ethnography, Language Learning